MEDIAN EPISIOTOMY APPROACH IN A MINIATURE POMERANIAN WITH VULVAL HYPOPLASIA: A CASE REPORT - S. Rangasamy; S. Sathishkumar; J. Umamageswari; R. Sureshkumar; D. Reena; S. Alagar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This case report details the episiotomy approach employed in managing vulval hypoplasia in a two year old Miniature Pomeranian bitch. The animal was presented to the Teaching Veterinary Clinical Complex, Veterinary Gynaecology and Obstetrical Unit, Madras Veterinary College, displaying a history of greenish black discharge and continuous straining for two hours. The animal was bred before 64 days. Physical examination revealed a small vaginal opening, measuring approximately 1.5 cm in length. Digital examination indicated fetal hind limbs and tail extending into the vaginal passage, while all other vital parameters were within the normal range. Attempts to induce uterine contractions using Inj. Oxytocin and 10 % Calcium gluconate in 5 % DNS proved unsuccessful. Therefore, under local anesthesia (2 % Lignocaine injection), median episiotomy was made and a single live male puppy was successfully delivered with mild traction. Closure of the incision site was accomplished using PGA 1/0 with a simple interrupted suture pattern. The patient had uneventful recovery after 5 day treatment regimen, involving a single dose of subcutaneous Inj. Cefovecin (antibiotic) and anti-inflammatory drugs, along with meticulous wound management.